LAW ENFORCEMENT AGAINST CRIMINAL ACTS OF FRAUD USING THE ONLINE INVITATION MODE - Ismiyanto, Ismiyanto (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2024)
The most popular case of online fraud is fraud using online invitation mode on social media. Law enforcement against criminal acts of fraud using online invitation mode is very important. Lack of strict and clear law enforcement is the trigger for this criminal act of fraud to continue to occur. This research aims to describe the regulation of criminal acts of fraud in Indonesian law and analyze law enforcement against criminal acts of fraud using the online invitation mode. This type of research is normative legal research. This research uses a statutory approach. The data source for this research uses secondary data. The data analysis technique used is qualitative data analysis technique. The research results show that criminal acts of fraud in Indonesian law are regulated in the Criminal Code and the Information and Electronic Transactions Law. In the Criminal Code, fraud is regulated in Chapter XXV Book II of the Criminal Code Articles 378-395 and specifically regulated in Article 378 of the Criminal Code, online fraud is regulated in Article 28 Paragraph (1) of the Information and Electronic Transactions Law. The online invitation mode for criminal fraud is relatively new. Law enforcement is carried out by the Police against perpetrators of fraud using the online invitation mode, namely arresting perpetrators who create online invitation applications. Law enforcers usually impose multiple articles as regulated in Article 378 of the Criminal Code and Article 28 Paragraph (1) of the Information and Electronic Transactions Law with the threat of imprisonment for a maximum of 6 (six) years and/or a fine of a maximum of IDR. 1,000,000. 000, to prove error, Article 5 and Article 6 of the Information and Electronic Transactions Law are used as recognition of information, documents and electronic signatures as valid evidence in court.Â